Stabilization of Peat Soil with Vegegrout - Syarif, Firman; Kurniawan, Mahadi; Ahmadi, Heri; Setiawan, Panji Rachmat (International Journal of Sustainable Construction Engineering and Technology, 2023)
A common issue in the construction industry is peat soil. Peat soil is very soft soil with a very low bearing capacity and is quickly compressible if the load is acting on it. Peat soil can produce significant ground settlement when loaded. This study added bacteria-producing vegetable waste to peat soil in order to assess how this addition affected the compressive strength of the peat soil. Vegetable waste is sourced from traditional markets in the city of Pekanbaru, while the original peat soil was acquired from Kualu Nenas Village, Kampar Regency, Province Riau. CaCl2 and urea are the additives that are employed. The variants of Vege waste to the specimen in the amounts of 0%, 15%, 20%, 25%, and 30%, the shear strength test was conducted. Results testing the physical properties of the original peat soil found that the soil originated from the village location Buana Makmur km 55, Dayun District, Siak Regency, is a type of peat soil with a water content of 351.092% and specific weight (Gs) = 1.530. the highest shear strength value is found in the addition of 20 % vege waste of 0,98 kg/cm2